Pemaknaan Setawar Sedingin Dalam Penyelesaian Konflik Pada Masyarakat Bengkulu - Alfarabi; Aldila Vidianingtyas Utami; Puji Haryadi Mulyana Sukma; Venti Puspitasari (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study on the "Setawar Sedingin Tradition in Bengkulu Society" aims to uncover the meaning of the Setawar Sedingin tradition within Bengkulu's traditional processions and explain the process by which it takes place. In this study, the researcher employed a qualitative method with a phenomenological approach to examine the meanings contained within Setawar Sedingin based on the real-life experiences of research informants, whom the researcher selected using a purposive sampling technique. To collect data, the researcher employed observation, interviews, and document searches related to Setawar Sedingin. Subsequently, the researcher employed data reduction and triangulation as data analysis techniques, and used data verification with research informants to validate the data. The results indicate that the Setawar Sedingin tradition is named after the leaves of the plant setawar and sedingin. Setawar and Sedingin have the meaning of offering and cooling down conflicts.